Healthcare costs of patients with cancer stratified by Khorana score risk levels. (1st January 2021) - Khorana, Alok A.; Kuderer, Nicole M.; McCrae, Keith; Milentijevic, Dejan; Germain, Guillaume; Laliberté, François; MacKnight, Sean D.; Lefebvre, Patrick; Lyman, Gary H.; Streiff, Michael B.
Abstract: Aims: Patients with cancer are at high risk of venous thromboembolism (VTE), which entails a high economic burden. The risk of cancer-associated VTE can be assessed using the Khorana score (KS), a validated VTE risk prediction algorithm. This study compared healthcare costs associated with different KS in a population of patients newly diagnosed with cancer. Methods: The Optum Clinformatics DataMart database (01/01/2012–09/30/2017) was used to select adult patients with ≥1 hospitalization or ≥2 outpatient claims with a cancer diagnosis (index date) initiated on systemic therapy or radiation therapy. Patients were classified in mutually exclusive cohorts based on KS (i.e. KS = 0, 1, 2 or ≥3). The observation period spanned from index to the earliest among the end of data availability, death, end of insurance coverage, or 12 months. Results: In total 6, 194 patients (KS = 0: 2, 488; KS = 1: 2, 125; KS = 2: 1, 074; KS ≥ 3: 507) were included. On average, patients were aged 68 years, 48–52% were female, and the Quan–Charlson comorbidity index ranged between 1.1 and 1.4. Over the observation period, all-cause total healthcare costs per patient per month (PPPM) were 8, 826 (KS = 0), 11, 598 (KS = 1), 14, 028 (KS = 2), and 16, 211 (KS ≥ 3). Using the KS = 0 cohort as a reference, adjusted PPPM costs were 2, 506, 4, 775, and 6, 452 higher in the KS = 1, KS = 2, and KS ≥ 3 cohorts, respectively. Hospitalization and outpatient costs were the main drivers of these differences. Similar results were found for VTE-related costs, which represented 4–11% of the total all-cause cost difference between KS cohorts. Limitations: Residual confounders; results may not be generalized to patients with other insurance plans or those who received treatments other than systemic therapy or radiation therapy. Conclusions: This real-world analysis found that cancer patients at higher risk of VTE (based on KS) incurred significantly greater all-cause and VTE-related healthcare costs compared with cancer patients at lower risk of VTE.